More than a t-shirt: The competitive nature of intramural sports - Marse, Atticus; Taylor, Brady; Carey, Rhys; Lee, Tommy; Biel, Leo; Mehrayin, Kian (My University, 2025)
Intramural athletes share how intensity, passion and pride drive games that are supposed to be “just for fun.”
Runtime 00:09:51